"Control interno al departamento administrativo y su relación con la captación de recursos económicos en la liga deportiva cantonal La Mana, año 2013" - Miranda Lema, Alex Washington (2016)
This research entitled "Internal Control to the administrative department and its relationship with the uptake of funds in the Liga Deportiva Cantonal La Maná, 2013" is located on the street Pujilí between San Pablo and Manabí, it was carried out in order to know the way how the organization has been handling the financial and material resources from public, private entities and natural persons, ie self-management. The objectives posed in this work were to analyze administrative policies and organizational structure, evaluate the feedback system of economic resources and verify compliance with the laws and regulations of the Cantonal Liga Deportiva La Maná. For the expected data types and applied research and descriptive, descriptive, inductive and analytical method and research techniques such as interviews and surveys were used, which were addressed to the President as the legal representative of the LDCLM and the members of the Board. The results showed that the Cantonal Liga Deportiva La Maná does have an adequate organizational structure for the development of administrative activities, the chart shows down-command levels from highest to lowest, the members of the institution must comply with the provisions of the regulation to achieve the institutional purpose under Law of Sports, Physical Education and Recreation of Ecuador, the Organic Law of the Comptroller General and internal bylaws. The collection system that uses financial resources is good for the institution 58.33% of respondents, this is due to inadequate existing computer software for recording administrative and financial activities according to 91.67% of the partners. Compliance with laws and regulations established by the supervisory bodies and rules of procedure is 80% reliability, while the level of risk is 20%